2020
DOI: 10.3390/agronomy10101521
|View full text |Cite
|
Sign up to set email alerts
|

Plant Sex Prediction Using Genetic Markers in Cultivated Yams (Dioscorea rotundata Poir.) in Benin

Abstract: Dioscorea rotundata Poir. is mainly dioecious but it also produces monoecious individuals. Recently two genetic markers were proposed to determine the sex in this species. We tested them in 119 individuals from 101 different cultivars of the national collection of Benin to verify whether they can predict the sex observed in the field. Among the analyzed individuals, 72 were male, 37 were female, 7 were monoecious and 3 were non-flowering. Our results showed that the marker sp16, associated with the W allele (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Previous reports demonstrated an involvement of chromosome 6, and secondary chromosomes 1 and 11, on D. alata flowering and sexual reproduction [ 3 , 5 ]. As hypothesized by Denadi et al [ 20 ], Dioscorea spp. flowering and sex might be controlled by several genes as our results also supported.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous reports demonstrated an involvement of chromosome 6, and secondary chromosomes 1 and 11, on D. alata flowering and sexual reproduction [ 3 , 5 ]. As hypothesized by Denadi et al [ 20 ], Dioscorea spp. flowering and sex might be controlled by several genes as our results also supported.…”
Section: Discussionmentioning
confidence: 63%
“…Tamiru et al [ 9 ] also identified a DNA marker, sp1, linked to the putative Z-linked region predicting maleness. Using these markers to predict sex at earlier growth phases among D. rotundata accessions has been reported [ 10 , 20 ]. However, these markers’ prediction accuracy is not always perfect in yam sex identification at the seedling stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sp16 marker only predicts the likelihood of femininity and may not be transferable to other species. Dinadi et al [72] showed that although the absence of sp16 marker confirms the male sex of the individuals, its presence does not allow sex discrimination. From their study, it appeared that the best determinant of stable male cultivars is the absence of the sp16 marker and that the best determinant of stable female cultivars is the AA genotype of the sp1 marker.…”
Section: Mating Designs and Pollination In Yam Breedingmentioning
confidence: 99%
“…From their study, it appeared that the best determinant of stable male cultivars is the absence of the sp16 marker and that the best determinant of stable female cultivars is the AA genotype of the sp1 marker. Further investigations are encouraged as sex determination in white Guinea yam would be controlled by more than one locus [72]. Electrochemical sex determination of D. zingiberensis and D. bulbifera plants using polydopamine-functionalized graphene sheets has been successful [73].…”
Section: Mating Designs and Pollination In Yam Breedingmentioning
confidence: 99%